Childfree Paradigm in Lampung and West Java Communities from Human Rights and Maqashid Shari'ah Perspectives - Mu'in, Fathul Mu'in; Miswanto, Miswanto; Febriati, Nurullia; Sakirman, Sakirman (Universitas Islam Negeri Raden Intan Lampung, 2024)
A paradigm shift in choosing not to have children (childfree) occurred in the communities of Lampung and West Java as well as in other areas. On the one hand, this choice is recognized as the right of every individual guaranteed by statutory regulations, on the other hand, this is considered not fully in accordance with one of the goals of marriage, procreation. Based on this, this problem becomes interesting to study in more depth in order to understand the phenomenon of childfree from the perspective of Human Rights (HAM) and maqashid shari'ah. The research method used is a qualitative method with an ethnographic approach, with data sources coming from childfree practitioners, books and scientific articles. The research results found that childfree practitioners choose not to have children based on various factors, such as economics, mental health, personal considerations, outlook on life, and environmental factors. From a human rights perspective, childfree is permitted because every individual has the right to privacy, including in making decisions about their personal and family lives, as mandated in Article 12 of the Universal Declaration of Human Rights. However, from the maqashid shari'ah point of view, childfree in normal husband and wife conditions is contrary to Islamic teachings because one of the goals of Islamic law is to preserve offspring.